Analisis Pembelajaran Elektronik Dan Pola Pikir Tumbuh Kembang Pada Ketangkasan Karyawan Serta Dosen STIE PBM - Effendy, Nazory (STREAMING, 2024)
This study aims to determine the effect of e-learning and growth mindset to workforce agility at Insurance Company XYZ. This study using qualitative approach as well as observation and interview to collect data and information about the problems that might be happen. This study conducted interviews with 5 persons who are the employees of Insurance Company XYZ.In this study it was found that there were various positive and negative impacts. Even tho, the results of this study show that e-learning and growth mindset have an effect on workforce agility at Insurance Company XYZ. Therefore, the researcher give the suggestion for Insurance Company XYZ is to always empower, motivate and provide moral support for the employees to be able to provide the best for the company and not give up easily at work.